Ação do processo de cicatrização de feridas na função endotelial sistêmica: um estudo em ratos normoglicêmicos e hiperglicêmicos - Sabadini, Camila Pereira (Universidade Federal de São Carlos, 2024)
Wound healing is a dynamic and complex process that begins as soon as the discontinuation of intact skin occurs. It is divided in four stages, which are hemostasis, inflammatory phase, proliferation phase and remodeling. In the control of each phase are involved humoral mediators as grow factors, nitric oxide (NO), cytokines and reactive oxygen species (ROS). Several pathophysiologies such as inflammation and hyperglycemia can disturb the wound healing process. In this case, the endothelial function mediated by NO, ROS and cytokines seems to be an important therapeutic target. The aim of this study was to evaluate if the wound healing process is able to interfere in the endothelial function of normoglycemic (NG) and hyperglycemic (HG). To this a 10 mm diameter lesion was performed on the back of 79 Wistar rats treated (HG) or not (NG) with 150 mg/kg alloxan monohydrated, a drug that induces hyperglycemia through increase of ROS. The concentration-effect curves of acetylcholine was conducted to study vascular reactivity and the serical levels of IL-6, TNF-α, IL-10 and NO of this animals were performed at Day -1 (animals without wound), Day 0 (day the injury was done – hemostasis phase), Day 4 (four days after the injury - inflammatory phase), Day 8 (eight days after surgery – proliferative phase) and Day 14 (fourteen days later surgery - remodeling phase). The results showed that the wound healing process can generate endothelial dysfunction (ED) in different phases to NG and HG rats, occurring in the hemostasis and inflammatory phases, respectively. Regarding the inflammatory profile, TNF-α and IL-6, the main mediators of the pro-inflammatory process in the wound healing, seem to be linked to the regulation of endothelial function in NG and HG rats in a different way. The concentration of ROS seems to be involved in this process, since serum NO concentrations did not directly influence the endothelial function of these rats during the wound healing process.
Action of the wound healing process on systemic endothelial function: a study in normoglycemic and hyperglycemic rats
Keywords: Cicatrização de feridas; Pele; Disfunção endotelial; Hiperglicemia; Reatividade vascular; Wound healing; Skin; Endothelial disfunction; Hiperglycemia; Vascular reactivity; CIENCIAS BIOLOGICAS::FARMACOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA